2015
DOI: 10.1080/14685248.2015.1031242
|View full text |Cite
|
Sign up to set email alerts
|

Spectral behaviour of the turbulence-driven power fluctuations of wind turbines

Abstract: Field and laboratory experiments were performed to unravel the structure of the power output fluctuations of horizontal-axis wind turbines based on incoming flow turbulence. The study considers the power data of three wind turbines of rotor sizes 0.12, 3.2, and 96 m, with rated power spanning six decades from the order of 10 0 to 10 6 W. The 0.12 m wind turbine was tested in a wind tunnel while the 3.2 and 96 m wind turbines were operated in open fields under approximately neutrally stratified thermal conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 36 publications
7
68
0
Order By: Relevance
“…The mean incoming velocity for all cases was U 0 = 8.5 m·s −1 , giving a Reynolds number based on the rotor diameter of Re = Ud/ν ∼ 7 × 10 4 , where ν is the kinematic viscosity, and a tip-speed ratio λ = ΩR/U 0 = 5. More details on the model turbine and its performance can be found in Tobin et al [22]. An active turbulence generator (TG) was used to induce large-scale and energetic coherent motions, resulting in high-turbulence (henceforth HT) intensity I HT = σ u /U 0 ≈ 11.5% at the turbine location.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean incoming velocity for all cases was U 0 = 8.5 m·s −1 , giving a Reynolds number based on the rotor diameter of Re = Ud/ν ∼ 7 × 10 4 , where ν is the kinematic viscosity, and a tip-speed ratio λ = ΩR/U 0 = 5. More details on the model turbine and its performance can be found in Tobin et al [22]. An active turbulence generator (TG) was used to induce large-scale and energetic coherent motions, resulting in high-turbulence (henceforth HT) intensity I HT = σ u /U 0 ≈ 11.5% at the turbine location.…”
Section: Methodsmentioning
confidence: 99%
“…In the third region-dominated by very large scales-the power fluctuations are found to be directly influenced by the flow. Recently, Tobin et al [22] established a tuning-free model for the transfer function G( f ), which shows robust performance across wind turbine sizes spanning from laboratory models to MW scales.…”
Section: Introductionmentioning
confidence: 99%
“…The tower was made of a 4 mm diameter threaded steel rod. Refer to Tobin et al [17] for similar setup. The winglets are made by extending and bending the blade's tip with a 4 mm radius of curvature and 4 mm out-of-plane height, giving a winglet length ∼ 6.7% of the turbine radius, while maintaining the rotor radius as projected in the axial direction.…”
Section: Model Turbinesmentioning
confidence: 99%
“…They suggested that the spectral content of the power fluctuations, Φ P , and that of the incoming flow, Φ u , exhibit a relationship that can be characterized by a nonlinear transfer function G( f ) ∝ f −2 across relevant length scales. Recently, Tobin et al [8] introduced a tuning-free model for such transfer function G( f ) for single turbines, which was tested across turbine sizes. Overall, this implies that accurate estimation of Φ u is essential for the estimation of the corresponding structure of the power fluctuations of wind turbines.…”
Section: Introductionmentioning
confidence: 99%